Վեստֆալյան համակարգը իբրև արդի եվրոպական քաղաքականության շրջադարձային հանգրվան - Եփրեմյան, Տիգրան (YSU Journal of International Affairs, 2015)
The paper comparatively analyzes and illustrates the transition of European politics from the medieval universal world order to the modern international relations system. The Peace of Westphalia (1648) was a turning point in the history of international relations. It symbolized the transformation from the system of political rule based on the hierarchical structures of medieval Christendom to the horizontal system of sovereign territorial states. Throughout the middle ages, the postRoman myth of the empire still had a great significance. The rising sense of national individualism was promoted by the Renaissance and Reformation, which replaced the Papacy and Empire upon which the hierarchies of western Christendom had been centered. As a result, after the Peace of Westphalia formalized relations between modern states based on mutual recognition of sovereignty displaced the criss-crossing relations between heterogeneous feudal and non-state actors organized by the hierarchical claims of the Empire and the Church. With the consolidation of the means of violence by sovereigns and the emergence of territorially bounded states, the European politics was differentiated into distinct domestic and international spheres. Thus, sovereign statesbecame the only legitimate political actors which were governed by sovereign rulers, acknowledging no rival authorities above them and none below. These processes affected the international dimension of conflict by furthering the fragmentation of Europe into distinct states. Around the states a new kind of political life – international politics– started to develop. The start of the secularization and its adjacent idea of selfdetermination entailed the principle of peaceful coexistence among legally equal members of international society. However, the concept of a universal world order remained on the political agenda, but it meant only the preeminence of a monarch within a system of fragmented and overlapping sovereignty rather than direct rule over a European super-state.
Keywords: Thirty Years’ War, Peace of Westphalia, modern state, sovereignty, world order, geo-political hierarchy, international anarchy, international system